INVENTARISASI TUMBUHAN BERKHASIAT OBAT DI DESA POKKANG, KEC. KALUKKU, KABUPATEN MAMUJU, PROVINSI SULAWESI BARAT - Hastuti Hastuti; Ika Lestari; Muhammad Yunus; Ahmad Hasyim (JURNAL BIOSENSE, 2022)
Back to nature is a trend that is being favored by people around the world, including Indonesia. The use of herbal ingredients and traditional medicine has become an inseparable part of Indonesian people's lives. This study aims to determine the types of medicinal plants used, the parts used and how to use them by the people of Pokkang village, Kec. Kalukku, Kab. Mamuju. This research is a qualitative descriptive study. with data collection techniques through interviews, observation and documentation. The research data were analyzed descriptively and presented in the form of descriptions and tables. The results showed that there were 28 species of medicinal plants used by the people of Pokkang village, Kec. Kalukku, Kab. Mamuju to treat disease. The plant parts used are leaves, fruit, stems, roots and rhizomes. The way to use medicinal plants is by brewing, boiling, kneading, grating and making fresh vegetables.